Antibacterial Effectiveness of A Combination of Anredera cordifolia (Ten.) Steenis and Strobilanthes crispus Blume Extract on Inhibition of the Growth of Streptococcus sp. Causes of Diabetic Ulcers - Khairani, Ulfiyah; Harlita, Tiara Dini; Aina, Ganea Qorry (Tropical Health and Medical Research, 2024)
Diabetic ulcers are open wounds on the skin surface due to macroangiopathy complications that become infected due to the entry of bacteria. Binahong and keji beling plants, can be used to treat diseases known as antibacterial and anti-inflammatory. This study aimed to determine the antibacterial effectiveness of a combination of binahong (Anredera cordifolia Ten. Steenis) and keji beling (Strobilanthes crispus Blume) extracts against Streptococcus sp. bacteria that cause diabetic ulcers. Samples were extracted using 96% ethanol solvent and then diluted the extract with a concentration variation of 25%, 50%, 75%, and 100%—antibacterial test using disc diffusion method (Kirby Bauer). Data analysis was used for the One-way ANOVA test and Duncan's Multiple Range Test further test method, which had a significance level of 0.05. Determination of antibacterial effectiveness was done by comparing the diameter of the most effective inhibition zone with the control antibiotic Ceftriaxone 30 µg. The results showed that the mean diameter of the inhibition zone of 25% concentration was 7.10 mm, and the inhibition zone of 100% concentration was 9.20 mm with moderate inhibition response. Statistical One Way Anova test showed that the combination of extracts affected the growth of Streptococcus sp. The most effective Concentration is at 100% concentration of 9.20 mm and antibacterial effectiveness of 92% with positive control Ceftriaxone 30 µg at 10.00 mm. It can be concluded that the combination of binahong and keji beling extracts can inhibit Streptococcus sp. bacteria, but its potential is not yet effective compared to Ceftriaxone 30 µg antibiotics